(untitled) (Journal of Universal Science Research, 2024)
In Tic-Tac-Toe of the classic game is built on computer-based flat form using python as apart of case study project using Artificial Intelligent techniques. The primary goal for this project is to create a computer artificial intelligent based on Tic-Tac-Toe 4x4 game that show two players on who will win and who will lose the game accordingly, using the standard Minimax algorithm, it was adopted and modified as a subset of rules from best gameplay practices: (1) attempt to win, (2) endeavor to keep a misfortune, (3) make a key move, and (4) make an irregular move. To make the game more fun and more winnable at easier difficulty levels, probabilities are introduced that the computer would find a valuable move and ignore it. In the end, the computer artificial intelligent uses a simple, lightweight decision tree to choose its next move, and the gameplay is fast, balanced, and enjoyable. furthermore, in the winning strategy in a chess game by means of symbolic model checking, and demonstrate the winning strategy in tic-tac-toe game through the symbolic model checking tool improved with the verification algorithm for winning strategy.